2019
DOI: 10.1101/2019.12.13.874362
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

YBEY is an essential biogenesis factor for mitochondrial ribosomes

Abstract: Ribosome biogenesis requires numerous trans-acting factors, some of which are deeply conserved. In Bacteria, the endoribonuclease YbeY is believed to be involved in 16S rRNA 3'-end processing and its loss was associated with ribosomal abnormalities. In Eukarya, YBEY appears to generally localize to mitochondria (or chloroplasts). Here we show that the deletion of human YBEY results in a severe respiratory deficiency and morphologically abnormal mitochondria as an apparent consequence of impaired mitochondrial … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 106 publications
1
3
0
Order By: Relevance
“…For reasons that are not clear, mitochondrial polysomes cannot be separated from monosomes under the experimental conditions used here. Similar observations have been made in other species including S. cerevisiae (41,42) and humans (43)(44)(45).…”
Section: Mti3 With the Mt-ssusupporting
confidence: 88%
“…For reasons that are not clear, mitochondrial polysomes cannot be separated from monosomes under the experimental conditions used here. Similar observations have been made in other species including S. cerevisiae (41,42) and humans (43)(44)(45).…”
Section: Mti3 With the Mt-ssusupporting
confidence: 88%
“…We found that smRNA bDNA FISH can be adapted for the detection and quantification of mitochondrially encoded rRNAs, low-abundance noncoding RNAs, and even short transcripts like tRNAs. We applied this technology for imaging the MT-CYB mRNA, the mitochondrial 12S rRNA, the mitochondrial tRNA Val , and the mirror RNAs for MT-CYB and 12S rRNA (17,18). As expected, 12S rRNA and tRNA Val (which is not only a transfer RNA but also a structural component of the mitoribosome (19)), were very abundant and nearly filled the entire mitochondrion (Fig.…”
Section: Introductionmentioning
confidence: 57%
“…Recent studies suggest that MAM33-family proteins might be involved in mitoribosome biogenesis. Indeed, they are linked to the LSU biogenesis in yeast (Hillman and Henry, 2019), in Trypanosoma, the recent structure of the SSU "assemblosome" includes a heterotrimeric p22, directly highlighting its role in mitoribosome biogenesis (Saurer et al, 2019;Sprehe et al, 2010) and in humans, the protein YBEY forms a complex with p32 and is involved in the SSU biogenesis (Summer et al, 2020). We observed that p32 is an integral component of the Chlamydomonas mitoribosome.…”
Section: Discussionmentioning
confidence: 72%
“…S4A). This MAM33-family protein is seemingly conserved in all eukaryotes, and has been described to have several functions in mitochondria, some related to mitoribosome assembly (Hillman and Henry, 2019;Jiang et al, 1999;Summer et al, 2020;Yagi et al, 2012). However, this is the first time that mS105/p32 has been identified as a core component of a ribosome.…”
Section: Overall Structure Of the Chlamydomonas Mitoribosomementioning
confidence: 99%